Implementasi Kebijakan Penjualan Liquifeid Petroleum Gas Tabung 3 Kilogram Sesuai Harga Eceran Tertinggi (Studi Di Kecamatan Luwuk Selatan Kabupaten Banggai) - Djohanis, Herni; Mustainah M; Nawawi Nasir (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The policy for selling 3 (three) kilogram Liquified Petroleum Gas Cylinders according to the highest retail price shows problems in the implementation process. The problems in question include, among other things, a lack of understanding of policy goals and objectives, a lack of resources, facilities and infrastructure, implementing agents who do not understand their main tasks and functions well, resulting in the policy implementation process not being optimal. By looking at the existing phenomena, the author conducted research, aiming to analyze and provide an overview of the Implementation of the Sales Policy for 3 (Three) Kilogram Liquified Petroleum Gas Cylinders According to the Highest Retail Price (Study in South Luwuk District). The location of this research includes South Luwuk District and the Natural Resources Section of the Regional Secretariat of Banggai Regency. The theory used in this research is the theory of Public Policy Implementation from Van Metter and Van Horn[1]. The research method uses a qualitative approach, and the informant selection technique uses purposive sampling. The number of research informants was 7 (seven) people. Data collection techniques are observation, interviews and documents. In accordance with the results of the discussion based on research facts, it was concluded that the Implementation of the Sales Policy for Liquified Petroleum Gas 3 Kilogram Cylinders According to the Highest Retail Price (Study in South Luwuk District) was not optimal. Because the six indicators of policy implementation, namely the size and objectives of the policy, resources, characteristics of implementing agents, attitudes/tendencies (disposition) of implementers, communication between organizations and implementing activities, as well as the state of the economic, social and political environment show that conditions are not going well.